2018
DOI: 10.1128/mbio.00319-18
|View full text |Cite
|
Sign up to set email alerts
|

Allometry and Ecology of the Bilaterian Gut Microbiome

Abstract: Classical ecology provides principles for construction and function of biological communities, but to what extent these apply to the animal-associated microbiota is just beginning to be assessed. Here, we investigated the influence of several well-known ecological principles on animal-associated microbiota by characterizing gut microbial specimens from bilaterally symmetrical animals (Bilateria) ranging from flies to whales. A rigorously vetted sample set containing 265 specimens from 64 species was assembled.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 70 publications
(118 reference statements)
4
42
1
Order By: Relevance
“…In reanalyzing Sherrill-Mix et al's [38] data, a similar phenomenon was also observed ( and an LOP-based nonparametric approach to fit ′ (). We will model the covariance…”
Section: Likelihood Formulationsupporting
confidence: 52%
See 1 more Smart Citation
“…In reanalyzing Sherrill-Mix et al's [38] data, a similar phenomenon was also observed ( and an LOP-based nonparametric approach to fit ′ (). We will model the covariance…”
Section: Likelihood Formulationsupporting
confidence: 52%
“…We analyzed gut bacterial 16S rRNA gene sequence data collected on 265 specimens from 64 species [38]. The bacterial lineages collected were placed into phylogenetic taxa, approximately including 65 families that are common to all animal species.…”
Section: Networking the Impact Of Microbiomes On Animal Evolutionmentioning
confidence: 99%
“…17 In addition, 16S rRNA gene qPCR was carried out on a subset of samples using primers and protocols previously described. 18 To identify bacteria (taxa) that are commonly associated with HAIs, we specifically queried sequences from practitioner stethoscope samples of sets A and C for the presence of Staphylococcus, Pseudomonas, Acinetobacter, Clostridium, Enterococcus, Stenotrophomonas, and Burkholderia genera. The 16S rRNA gene sequences assigned to these genera in the QIIME pipeline were then manually aligned to the NCBI 16S rRNA sequence database with BLAST to confirm genus identity and, if possible, to generate species-level assignment.…”
Section: Bacterial Amplification Sequencing and Analysismentioning
confidence: 99%
“…1 ). In mammalian microbiome studies, there is often a strong correlation between host phylogeny and diet, making it difficult to parse apart the effects of diet and phylogeny on microbiome evolution ( 28 ). Bats provide a potential solution to this issue, because several feeding modes have evolved in parallel two or more times within the order.…”
Section: Bats Are Taxonomically and Ecologically Diversementioning
confidence: 99%